Язык и культура: некоторые аспекты исторических и современных контактов славянских и еврейских языков - Матвeeв В. И. (Kalbotyra, 1992)
Taking into account the artifical formation of modern Ivrit, great number of borrowings often lacking even semitic roots, as well as complicated and varied ethnolinguistic situation in modern polylinguistic Israel, it’s possible to speak about the formation of specifically new culture, accepting the elements of different cultures /Slavonic included/, being greatly enriched in this process.